Solution
prove
Solution
Solution steps
Manipulating left side
Factor
Factor out common term
Factor
Rewrite as
Rewrite as
Apply exponent rule:
Apply Difference of Two Squares Formula:
Factor
Rewrite as
Apply Difference of Two Squares Formula:
Rewrite using trig identities
Use the Pythagorean identity:
Simplify
Expand
Apply Difference of Two Squares Formula:
Apply rule
Use the Pythagorean identity:
Simplify
Apply rule
Expand
Apply the distributive law:
Apply exponent rule:
Add the numbers:
Add similar elements:
We showed that the two sides could take the same form
Popular Examples
prove sin(-x)cos(pi/2-x)=(cos(2x)-1)/2prove prove cos(b)+sin(b)tan(b)=sec(b)prove prove 2sin(2θ)(1-2sin^2(θ))=sin(4θ)prove prove cos^2(x)csc^2(x)=cot^2(x)prove prove ((cos^2(x)))/(1-sin(x))=1+sin(x)prove
Frequently Asked Questions (FAQ)
Is cos^4(w)+1-sin^4(w)=2cos^2(w) ?
The answer to whether cos^4(w)+1-sin^4(w)=2cos^2(w) is True